Transient Brugada-Like Electrocardiogram Configuration Provoked by COVID-19 Fever - May Honey Ohn; Jun Rong Ng; Khin Maung Ohn; Pan Nyein Han (UMS, 2023)
There are varieties of cardiac complications which can occur in COVID-19 encompassing acute coronary syndrome, myocarditis to arrhythmia. We report a case of COVID-19 infected patient who presented with a high fever which provokes transient Type 1 Brugada-like ECG configuration. Brugada syndrome is a potentially life-threatening arrhythmia which could lead to sudden cardiac death secondary to ventricular arrhythmias. Being commonly asymptomatic, there are many triggers which could lead to its manifestations and subsequent complications. While fever, being one of the triggers, is the most common presentation of COVID-19. Besides, it could be multifactorial, either from the variant systemic complications in COVID-19 or from the management itself, especially common drugs used in resuscitation which could provoke the Brugada pattern. Looking at this association, ECG monitoring then becomes important in COVID-19, especially in those with chest pain and fever. Proper treatment for fever in COVID-19 is prudent to avoid malignant arrhythmia.